STRENGTHENING VILLAGE INNOVATION SPACES THROUGH GEOGRAPHIC COMMUNICATION AND PLACE-BASED LEADERSHIP: EVIDENCE FROM PANGGUNG HARJO AT COVID-19 PERIOD - Gabriele Benita Aprilia; Seno Budhi Ajar (Universitas Sebelas Maret (UNS), 2026)
The development of technology in today's era is one of the factors causing the emergence of local leaders who are placelessness or not oriented towards place. Regional leaders must have a Place-based principle to improve the welfare of the local community by developing village innovation while still using local strengths. Panggungharjo Village, located in Sewon District, was named the Best and Inspiring Village because the village head implemented place-based leadership. This study uses a qualitative approach with a thematic method. Data collection was carried out through Elite Interviewing of village government and village enterprise, field observations, document archives, and online data search techniques. The focus of this study is on the communication patterns that occur in the Panggungharjo Village Government in creating relational space in the form of place-based village innovation. Based on the results of the study, Panggungharjo Village has the innovations KUPAS, Pasardesa.id. and Pasti Angkut. The geographic communication that is formed is between the village head, the community, and third parties in solving the waste problem. Place-based leadership from the three innovations is formed because of the fields of political, community, business, union, and managerial leadership. The innovation space that is formed is the integration of real space and cyberspace applied in the innovations KUPAS, Pasardesa.id, and Pasti Angkut